Community stressors (violence, victimization, and neighborhood disorder) with cardiometabolic outcomes in urban Jamaica - Gary-Webb, Tiffany L.; Dyer, Harika; Mckenzie, Joette; Younger-Coleman, Novie; Tulloch-Reid, Marshall; Blake, Alphanso; Govia, Ishtar; Bennett, Nadia; McFarlane, Shelly; Wilks, Rainford J.; Williams, David R.; Ferguson, Trevor S. (Frontiers in Public Health, 2023)
Background: Despite limited data on neighborhood factors and health risk in Caribbean populations, previous analyses from Jamaica have shown that neighborhood and home disorder were associated with lower physical activity and higher cumulative biological risk among women, while poorer neighborhood infrastructure was associated with higher overweight/obesity among men. Design: Cross-sectional survey design Objectives: In this study, we explored whether community stressors, as measured by community violence, victimization and neighborhood disorder scores, were associated with cardiometabolic outcomes (obesity, diabetes, hypertension and high cholesterol) in urban Jamaican communities. Sex-specific Poisson regression models were used to estimate prevalence ratios (PR) for these associations, adjusting for age, education, diet, physical activity and smoking. Participants: Of the 849 participants (M=282; F=567), mean age was 48 ± 18.5 years and most had at least a high school education. Men were more likely to be current smokers (29.4 vs 10.6%) and adequately physically active (53.2 vs 42.0%); more women were obese (46.0 vs. 19.0%), more likely to have hypertension (52.9 vs. 45.4%) and had high cholesterol (34.2 vs. 21.6%) (all p<0.05). Results: We observed significant associations only for those in the middle tertile of neighborhood disorder with prevalence of higher cholesterol [PR:1.72 (1.20 to 2.47)] in women and lower prevalence of obesity [PR:0.24 (0.10 to 0.53)] in men. Conclusions: Future work will explore additional approaches to measuring neighborhood characteristics in Jamaica and the mechanisms that may underlie any relationships that are identified.